Scenario of access to physiotherapeutic treatment of individuals affected by Cerebral Vascular Accident: An integrative review (Research, Society and Development, 2023)
The objective of this review was to identify in the literature the factors that limit the access of post-stroke individuals to physiotherapeutic treatment in health systems. The search was carried out in the following databases: PubMed, Scopus, BVS, Cochrane, Embase, Pedro and Scielo and, in order to complement the search, gray literature (Google Academic) was used. The following search terms were used: “strokes”, “therapeutic”, “publichealth”, “accesshealthservices”, “physiotherapy” present in Mesh and DeCS. The search included articles from the last 6 years, in Portuguese, English and Spanish. 1991 articles were found, after applying the criteria for inclusion and elimination of duplicates, 13 articles were analyzed, in which 10 answered the research question. The analyzed studies pointed out difficulties in accessing physiotherapeutic rehabilitation, the barriers that prevent admission were similar, being lack of referral, difficulty in moving to rehabilitation centers, unavailability of vacancy, bureaucracy in scheduling and long waiting time. In general, it was seen that there are still difficulties to get treatment, in which, according to the studies, access to physiotherapeutic treatment was seen as difficult to reach and insufficient, being related to financial, physical and bureaucratic issues. In this way, the studies carried out allowed us to know the status of post-stroke patients' access to physiotherapeutic care, which enables the development of strategies aimed at improving accessibility to rehabilitation services.